BOTTOM-UP DAN SATGAS-PELAJAR (Dominasi Social Promoted dalam Implementasi Kebijakan Penanganan Tawuran Pelajar di Kota Bogor) - , MAULANA ARIEF KUNCORO, Dr. Mada Sukmajati, MPP. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
There are so many public policies that have been produced by local government after power transfer from central government. One of public policy is about student street fighting (tawuran). in Bogor, author found interesting public policy in dealing with student tawuran. The public policy did not only explain administration process but also explain politic dynamic of formulation and implementation. It overrides state promoted paradigm that in general involve in policy and emphasize social capital as product resulted by people. Main element of the policy is establishment of student task force that place student task force to deal with student tawuran in Bogor. Implementation of student task force is not only administration process with authoritative decision, but is a political process that continuously involves negotiation. Complex and dynamic student street fighting places implementation of student task force in changing and unpredictable situation. In result it may fail. Did student task force born from bottom-up process consider implementability, which has synergy between policy content and context of its implementation? The concern guide author on research question: why did student task force become main element in dealing with student street fighting in Bogor? This research used some though frames: policy implementation, top-down vs bottom-up model, bottom-up model in policy implementation. Policy implementation is presented to explain how student tawuran occur in Bogor as context of policy. With bottom-up approach, author discovers participation of teacher as actors having knowledge, insight on student street fighting issue. It plays role in context implementation that will influence context of policy. Content of policy and context implementation in policy implementation is used to see why student task force becomes main element in dealing with student street fighting in Bogor. Then, this research used qualitative method with case study design. Accurate data was obtained by integrating data source3 through interview, document and observation. The three data was obtained with formal and informal ways. The research found that student street fighting in Bogor has occurred since 1995. Change in governmental system from centralistic to decentralistic system influenced student street fighting in Bogor. It may be concern of teacher. Teacher movement to deal with student street fighting reflected increase in people participation in public policy. In its end of struggle, teachers try to influence decision making that result in a policy of student task force. The policy was created from implementation process to deal with student street fighting by society. It is an institution having bottom-up spirit in agenda setting, formulation and implementation. An innovative policy that can adjust in development and progress of student street fighting in Bogor. It is a policy having synergy between implementation context and policy content that can deal with student street fighting in Bogor.